A rare presentation of neurofibromatosis 2 as quadriparesis - Hirolikar, Rushikesh S.; Bokade, Vishal B.; Ganwani, Amit; Khandait, Vinod (International Journal of Research in Medical Sciences, 2023)
Neurofibromatosis (NF) is a complex genetic disorder primarily recognized for its characteristic tumors affecting the nervous system and skin. We present an exceptional case of a patient diagnosed with NF type 2, exhibiting an atypical clinical manifestation-quadriplegia. This case underscores the rarity of such a presentation, as NF typically presents with neurocutaneous features such as café-au-lait macules, neurofibromas, and meningiomas. Our patient, a 46-year-old male, presented with gradual onset quadriplegia without any preceding symptoms of NF. Radiological evaluation revealed meningiomas as well as extensive spinal neurofibromas compressing the spinal cord. This case exemplifies the importance of considering NF as a differential diagnosis in patients presenting with unexpected neurological deficits. Timely recognition and management of such cases are crucial for preventing irreversible neurological damage. This report adds to the growing body of knowledge regarding the diverse clinical presentations of NF and emphasizes the need for comprehensive assessment and multidisciplinary collaboration in managing this intricate disorder within the realm of medicine.